Microwave fluidized bed for biomass pyrolysis. Part II: Effect of process parameters. (17th May 2017) - Adam, Mohamed; Beneroso, Daniel; Katrib, Juliano; Kingman, Sam; Robinson, John P.
Abstract: The microwave fluidized bed process developed in Part I (DOI: 10.1002/bbb.1780), in which the heating heterogeneity issues are overcome, has been applied to the pyrolysis of biomass. The degree of pyrolysis was established by studying the behavior of sycamore and pine under different operational conditions. Homogeneous heating was obtained, and it is shown that larger particles undergo more pyrolysis within the fluidized bed, consistent with the Biot number. Two limiting values of fluidization velocity were identified, a higher value above which unhydrolyzed particles are entrained with the fluidizing gas and a lower value below which thermal runaway takes place before fluidization. Theoretical correlations for minimum fluidization velocity were found to be unreliable for the biomass used within this study. The energy consumption obtained with optimal process parameters was found to be 3.5–4.2 kJ g −1 to obtain 60–70% of pyrolyzed solid, which is comparable with conventional pyrolysis and presents a significant opportunity for the scale‐up of a microwave fluidized bed. The use of a cold fluidizing gas promoted heat losses from the particles and increased the energy consumption; however, it prevented undesired thermal runaway effects. Pine and sycamore required different fluidization velocities and corresponding energy requirements, which was due to the fibrous nature of the feedstock. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd